The Grip Concept of Incisional Hernia Repair—Dynamic Bench Test, CT Abdomen With Valsalva and 1-Year Clinical Results - Kallinowski, Friedrich; Gutjahr, Dominik; Harder, Felix; Sabagh, Mohammad; Ludwig, Yannique; Lozanovski, Vladimir J.; Löffler, Thorsten; Rinn, Johannes; Görich, Johannes; Grimm, Annette; Vollmer, Matthias; Nessel, Regine (Frontiers in Surgery, 2021)
Incisional hernia is a frequent consequence of major surgery. Most repairs augment the abdominal wall with artificial meshes fixed to the tissues with sutures, tacks or glue. Pain and recurrences plague at least 10 - 20 % of the patients after repair of the abdominal defect. How should a repair of incisional hernias be constructed to achieve durability? Incisional hernia repair can be regarded as a compound technique. The biomechanical properties of a compound made of tissue, textile and linking materials vary to a large extent. Tissues differ in age, exercise levels and comorbidities. Textiles are currently optimized for tensile strength, but frequently fail to provide tackiness, dynamic stiction and strain resistance to pulse impacts. Linking strength with and without fixation devices depends on the retention forces between surfaces to sustain stiction under dynamic load. Impacts such a coughing or sharp bending can easily overburden clinically applied composite structures and can lead to a breakdown of incisional hernia repair. Our group developed a bench test with tissues, fixation and textiles using dynamic intermittent strain (DIS) which resembles coughing. Tissue elasticity, the size of the hernia under pressure and the area of instability of the abdominal wall of the individual patient was assessed with low-dose computed tomography of the abdomen preoperatively. A surgical concept was developed based on biomechanical considerations. Observations in a clinical registry based on consecutive patients from four hospitals demonstrate low failure rates and low pain levels after one year. Here, results from the bench test, the application of CT abdomen with Valsalva’s maneuver, considerations of the surgical concept and the clinical application of our approach are outlined.